2014
DOI: 10.1504/ijbra.2014.062996
|View full text |Cite
|
Sign up to set email alerts
|

Discovering non-coding RNA elements in Drosophila 3' untranslated regions

Abstract: The Non-Coding RNA (ncRNA) elements in the 3′ Untranslated Regions (3′-UTRs) are known to participate in the genes’ post-transcriptional regulations. Inferring co-expression patterns of the genes through clustering these 3′-UTR ncRNA elements will provide invaluable insights for studying their biological functions. In this paper, we propose an improved RNA structural clustering pipeline. Benchmark of the new pipeline on Rfam data demonstrates over 10% performance improvements compared to the traditional hierar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…For example, thousands of long ncRNAs (lncRNAs) were found using deep sequencing [ 25 27 ]. A study focusing on 3’-untranslated regions (UTRs) found 184 ncRNA clusters [ 28 ]. A quarter of the genomic regions that currently lack annotated genes, i.e., that are currently considered “intergenic”, show transcriptional activity (according to the intersection of the current annotation [ 29 ] and a genome-wide tiling array study [ 30 ]).…”
Section: Introductionmentioning
confidence: 99%
“…For example, thousands of long ncRNAs (lncRNAs) were found using deep sequencing [ 25 27 ]. A study focusing on 3’-untranslated regions (UTRs) found 184 ncRNA clusters [ 28 ]. A quarter of the genomic regions that currently lack annotated genes, i.e., that are currently considered “intergenic”, show transcriptional activity (according to the intersection of the current annotation [ 29 ] and a genome-wide tiling array study [ 30 ]).…”
Section: Introductionmentioning
confidence: 99%
“…However, in recent years, it has been found that these regions contain functionally important elements ( Cai, 2016 ) and independent transcription of miRNAs with their own promoters ( Hess et al, 2006 ). Intergenic regions may also contain unidentified functional elements, such as non-coding RNA ( Zhong et al, 2014 ; Fariha and Changrui, 2019 ). It is currently believed that intergenic regions can control gene expression and inhibition, and help RNA to identify genes with low conservation and diversity ( Ingvarsson et al, 2016 ; Bakhtiarizadeh and Salehi, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…can be used to perform all-against-all alignments on these RNA transcripts, which will then be subsequently summarized as the distance matrix for clustering purposes. Various clustering algorithms [ 8 , 39 ] can then be applied to identify ncRNA families with similar secondary structures and infer their amazing cellular and molecular functionalities.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, genome-wide RNA structurome analysis has led to many interesting discoveries regarding novel regulatory mechanisms. For example, analysis of the RNA structural elements in Drosophila melanogaster 3’-UTR suggests a cluster of ncRNA elements that can direct the localization of their upstream genes within the spermatids [ 8 ]. Similar studies have also been applied to the Ciona intestinalis genome for novel ncRNA family discovery [ 9 ].…”
Section: Introductionmentioning
confidence: 99%